Youth Policy and Extremism Prevention Tasks - S. Chernyavskiy (Международная аналитика, 2018)
The article analyses the main causes and factors of the militant extremist ideas spread among the youth. The author proposes measures necessary to counteract it and makes comments on the Russian state youth policy which is aimed at involving young people in social practice and informing them of the potential for their development, encouraging creative youth activity, reintegrating young people who find themselves in a difficult life situation into society. The article traces the main causes and factors of the spread of militant extremism ideas among the youth. Proposals are formulated on the measures necessary to counteract it, comments are made on the content of the Russian state youth policy aimed at involving young people in social practice and informing them of the potential for their development, the encouragement of creative youth activity, the reintegration of young people who find themselves in a difficult life situation into society